PERAN PENGELOLAAN APBD YANG EFEKTIF DAN EFISIEN DALAM MENDORONG KESEJAHTERAAN EKONOMI DI KABUPATEN MADIUN - Kurniawan, Mohammad Ricko; Sitohang, Arga Christian (Jurnal Nirta : Inovasi Multidisiplin, 2024)
The Regional Revenue and Expenditure Budget (APBD) is one of the important instruments for local governments in carrying out various development programs,  The main problem in the management of the Madiun Regency APBD during the 2018-2023 period is the mismatch between the realization of regional revenue and expenditure. This study uses a descriptive quantitative approach. Using a multiple linear regression model with time series data. The purpose of this study is to analyze the influence of the Effectiveness and Efficiency of the APBD that contributes to the welfare of the community in Madiun Regency. The results of this study show that the effectiveness and efficiency in the management of the Regional Revenue and Expenditure Budget (APBD) has a significant impact on the welfare of the people in Madiun Regency.